Polymorphic nonlinear optical crystal material of 3-amino-1, 2, 4-triazole nitrate as well as preparation and application of polymorphic nonlinear optical crystal material
By preparing 3-amino-1,2,4-triazole nitrate polymorphic nonlinear optical crystal materials, the problem of coordinated optimization of optical band gap, frequency doubling effect and birefringence in the existing technology is solved, and an efficient ultraviolet laser frequency doubling effect is achieved, which is suitable for ultraviolet laser frequency doubling crystal devices.
Patent Information
- Application Number
- CN202510220132.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-02-27
AI Technical Summary
Existing nonlinear optical crystal materials face challenges in synergistically optimizing the constraints between optical band gap, frequency doubling effect and birefringence, making it difficult to meet application requirements in the ultraviolet band.
The polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate was prepared by the slow volatilization method of aqueous solution. By regulating the ratio of organic source, inorganic source and water, two crystal forms, α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3), were formed, achieving a large frequency-harmonic effect, wide ultraviolet transmittance and moderate birefringence.
The prepared crystal materials show significant application potential in the field of ultraviolet laser frequency-doubling crystal devices. The frequency-doubling effects of α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3) are 3.5 times and 1 times that of KDP crystals, respectively. The ultraviolet transmission and absorption cutoff edges reach 240nm and 248nm, respectively. The birefringence is 0.069 and 0.046, achieving phase matching.
Smart Images

Figure CN120738769A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials and relates to a polycrystalline nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate and a preparation and application thereof. Background Art
[0002] As a key optoelectronic functional material, the core feature of second-order nonlinear optical crystals is the double-frequency effect (SHG), which makes them have important application value in the fields of frequency doubling devices, electro-optical modulators and holographic storage elements. Currently, nonlinear optical crystals that are widely used in the market include KH2PO4 (KDP), LiB3O5 (LBO), β-BaB2O4 (BBO), etc. With the rapid development of ultraviolet laser technology in high-end fields such as micromachining, high-density storage and lithography, the development of frequency doubling crystals suitable for the ultraviolet band has become a research frontier in materials science. However, how to synergistically optimize the restrictive relationship between the optical band gap, the frequency doubling effect and the birefringence remains the core challenge in the research and development of ultraviolet frequency doubling materials. The patent of this invention is proposed precisely to address the above challenges. Summary of the Invention
[0003] The present invention aims to provide a 3-amino-1,2,4-triazole nitrate polymorphic nonlinear optical crystal material having a large harmonic effect, wide ultraviolet transmittance and moderate birefringence, as well as a preparation method and application thereof.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] One of the technical solutions of the present invention provides a polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate, which includes two crystal forms: α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3).
[0006] Furthermore, for the crystalline form α of 3-amino-1,2,4-triazole nitrate, its chemical formula is (C2H5N4)(NO3), its molecular weight is 147.11, it crystallizes in the triclinic system, its space group is P1, and its unit cell parameters are α=110.44~114.63°,β=93.04~97.71°,γ=93.49~97.64°,Z=2,unit cell volume is
[0007] The crystal structure of the α-phase 3-amino-1,2,4-triazole nitrate is as follows: anion (NO3) - The unit is bonded to four adjacent (C2H5N4) +The adjacent two-dimensional layers are connected to form a two-dimensional van der Waals layered structure, and the adjacent two-dimensional layers are stacked in parallel on the bc plane in an -A1A1A1A1- stacking mode through van der Waals force interaction, eventually forming a pseudo three-dimensional structure ( Figure 1 ).
[0008] Furthermore, for the crystalline form β of 3-amino-1,2,4-triazole nitrate, its chemical formula is (C2H5N4)(NO3), its molecular weight is 147.11, it crystallizes in the monoclinic system, its space group is P21, and its unit cell parameters are β=88.32~92.14°,Z=8,unit cell volume is
[0009] The crystal structure of the β-phase 3-amino-1,2,4-triazole nitrate is as follows: anion (NO3) - The unit is bonded to four adjacent (C2H5N4) + The adjacent two-dimensional layers are stacked in parallel on the bc plane in a stacking mode of -A1A2A3A4- through the interaction of van der Waals forces, eventually forming a pseudo three-dimensional structure ( Figure 9 ).
[0010] The second technical solution of the present invention provides a method for preparing a polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate, wherein:
[0011] For α-phase 3-amino-1,2,4-triazole nitrate, it is prepared by a slow volatilization method of aqueous solution. Raw materials containing organic source, inorganic source and water are mixed, placed in an open evaporating dish, and slowly evaporated to obtain colorless and transparent flaky crystals, which are the target product.
[0012] Furthermore, in the raw materials, the molar ratio of the organic source, the inorganic source and water is 10:(10-60):(500-1250). Preferably, the molar ratio of the organic source, the inorganic source and water is 10:(10-30):(700-1050).
[0013] Furthermore, the crystallization temperature is 10° C. to 45° C. Preferably, the crystallization temperature is 15° C. to 30° C.
[0014] Furthermore, the crystallization time is not less than 7 days. Preferably, the crystallization time is 14 to 21 days.
[0015] Furthermore, the organic source is 3-amino-1,2,4-triazole.
[0016] Furthermore, the inorganic source is nitric acid.
[0017] For the β-phase 3-amino-1,2,4-triazole nitrate, it is prepared by a slow volatilization method of aqueous solution. Raw materials containing an organic source, an inorganic source and water are mixed, placed in an open evaporating dish, and slowly evaporated to obtain colorless and transparent flaky crystals, which are the target product.
[0018] Furthermore, in the raw materials, the molar ratio of the organic source, the inorganic source and water is 10:(70-120):(500-1250). Preferably, the molar ratio of the organic source, the inorganic source and water is 10:(90-100):(700-1050).
[0019] Furthermore, the crystallization temperature is 10° C. to 45° C. Preferably, the crystallization temperature is 15° C. to 30° C.
[0020] Furthermore, the crystallization time is not less than 7 days. Preferably, the crystallization time is 14 to 21 days.
[0021] Furthermore, the organic source is 3-amino-1,2,4-triazole.
[0022] Furthermore, the inorganic source is nitric acid.
[0023] The third technical solution of the present invention provides the application of 3-amino-1,2,4-triazole nitrate second-order nonlinear optical crystal material in laser frequency converters, optical parametric oscillators, optical parametric amplifiers and photoelectric rectifiers.
[0024] Furthermore, this second-order nonlinear optical crystal material can be used in laser frequency converters, which can output 532nm laser under 1064nm laser irradiation. The powder harmonic generation intensities of α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3) are 3.50 times and 1.00 times that of KDP crystal, respectively, and both can achieve phase matching.
[0025] The present invention proposes a method for compounding two π-conjugated planar elements, and successfully prepares two polycrystalline phases of 3-amino-1,2,4-triazole nitrate (α-, β-(C2H5N4)(NO3)) by slow volatilization technology from aqueous solution. Among them, α-, β-(C2H5N4)(NO3) have strong frequency-doubling effect (3.5×KDP(α-(C2H5N4)(NO3)), 1.0×KDP(β-(C2H5N4)(NO3))), wide band gap (5.17eV(α-(C2H5N4)(NO3), 5.00eV(β-(C2H5N4)(NO3))) and moderate birefringence (0.069(α-(C2H5N4)(NO3)), 0.046(β-(C2H5N4)(NO3)), and have important application potential in the field of ultraviolet laser frequency-doubling crystal devices.
[0026] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:
[0027] (1) This application provides for the first time two polymorphs of 3-amino-1,2,4-triazole nitrate and their use as second-order nonlinear optical crystal materials. Among them, the α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3) crystal materials both have a large frequency doubling effect, which is 3.5 times and 1 times that of KDP crystal, respectively, and can achieve phase matching. In addition, the ultraviolet transmission absorption cutoff edges of the crystal materials reach 240nm and 248nm, respectively. The two crystal materials show significant application potential in the field of nonlinear optics.
[0028] (2) This application provides a method for preparing the aforementioned crystalline material, wherein 3-amino-1,2,4-triazole nitrate crystals are prepared by a slow volatilization method using an aqueous solution. By precisely controlling the ratio of the starting materials, high-purity, controllable synthesis of different crystalline phases is achieved. This method has the advantages of mild synthesis conditions, high yield, and ease of crystal growth, and can produce millimeter-scale single crystals of high optical quality and excellent purity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the crystal structure of α-(C2H5N4)(NO3);
[0030] Figure 2 The X-ray diffraction pattern of sample 1-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the X-ray diffraction pattern of sample 1-1# after it was ground into powder;
[0031] Figure 3 is the UV-visible-near-infrared transmission spectrum of sample 1-1#;
[0032] Figure 4 is the infrared spectrum of sample 1-1#;
[0033] Figure 5 This is the thermogravimetric analysis spectrum of sample 1-1#;
[0034] Figure 6 This is the second harmonic signal diagram of sample 1-1# and standard sample KDP in the size range of 200 to 280 μm;
[0035] Figure 7 This is the second harmonic phase matching diagram of sample 1-1# in the 1064nm band;
[0036] Figure 8This is a birefringence test chart, where (a) the image of α-(C2H5N4)(NO3) when it is not extinguished; (b) the image of α-(C2H5N4)(NO3) when it is completely extinguished; and (c) the crystal thickness of α-(C2H5N4)(NO3).
[0037] Figure 9 It is a schematic diagram of the crystal structure of β-(C2H5N4)(NO3);
[0038] Figure 10 The X-ray diffraction pattern of sample 2-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the X-ray diffraction pattern of sample 2-1# after it was ground into powder;
[0039] Figure 11 This is the UV-Vis-NIR transmission spectrum of sample 2-1#;
[0040] Figure 12 This is the infrared spectrum of sample 2-1#;
[0041] Figure 13 This is the thermogravimetric analysis spectrum of sample 2-1#;
[0042] Figure 14 This is the second harmonic signal diagram of sample 2-1# and standard sample KDP in the range of 200 to 280 μm;
[0043] Figure 15 This is the second harmonic phase matching diagram of sample 2-1# in the 1064nm band;
[0044] Figure 16 These are diagrams of birefringence tests, including (a) the image of β-(C2H5N4)(NO3) when it is not extinguished; (b) the image of β-(C2H5N4)(NO3) when it is completely extinguished; (c) the crystal thickness of β-(C2H5N4)(NO3); Figure 17 Schematic diagram of the crystal structure of α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3). DETAILED DESCRIPTION
[0045] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0046] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0047] Example 1
[0048] (1) Preparation of samples 1-1# to 1-8#
[0049] An organic source (3-amino-1,2,4-triazole), an inorganic source (nitric acid), and water were mixed in a specific ratio to form a raw material. The mixture was placed in an open evaporating dish. After the aqueous solution slowly evaporated at the crystallization temperature, the solution was filtered, washed, and dried to obtain colorless, flaky α-(C2H5N4)(NO3) crystals. The relationship between the types and ratios of the raw materials in the initial mixture, the crystallization temperature, the crystallization time, and the sample number is shown in Table 1.
[0050] (2) Crystal structure analysis of samples
[0051] The structures of samples 1-1# to 1-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0052] The single crystal X-ray diffraction was performed on a Bruker D8 VENTURE CMOS X-ray single crystal diffractometer. The crystal size was 0.44 × 0.18 × 0.09 mm. 3 The data collection temperature was 293K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure was solved using the SHELXTL-97 program package; the positions of heavy atoms were determined by direct method, and the coordinates of the remaining atoms were obtained by difference Fourier synthesis method; the F-based 2 The coordinates of all atoms and anisotropic thermal parameters were refined using the full-matrix least-squares method.
[0053] Table 1. Relationship between sample synthesis conditions and sample numbers
[0054]
[0055] Single crystal X-ray diffraction results show that samples 1-1# to 1-8# have the same chemical formula and crystal structure, the chemical formula is α-(C2H5N4)(NO3), the molecular weight is 147.11, crystallizes in the triclinic system, the space group is P1, and the unit cell parameters are α=110.44~114.63°,β=93.04~97.71°,γ=93.49~97.64°,Z=2,unit cell volume is
[0056] Take sample 1-1# as a typical example, its crystal structure data is α=112.131(16)°,β=95.625(19)°,γ=95.861(18)°,Z=2,unit cell volume is Its crystal structure is Figure 1 shown.
[0057] Powder X-ray diffraction was performed on a Bruker D8 X-ray powder diffractometer from Bruker, Germany, using a fixed-target monochromatic light source of Cu-Kα and a wavelength of The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.
[0058] The powder X-ray diffraction results show that the diffraction peaks of samples 1-1# to 1-8# in the XRD spectra are at the same position as the diffraction peaks fitted by the single crystal data.
[0059] Take sample 1-1# as a typical example. Figure 2 The X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction and the X-ray diffraction pattern obtained by powdered sample 1-1# show consistent peak positions and intensities, indicating that the obtained sample is of high purity.
[0060] (3) UV-visible-near infrared spectroscopy test
[0061] The UV-visible transmission spectrum of sample 1-1# was tested on a Carry 5000 UV-visible-near-infrared spectrophotometer from Agilent Technologies, USA. Figure 3 As shown, the ultraviolet absorption cutoff edge of the compound is 240nm and the optical band gap is 5.17eV.
[0062] (4) Infrared spectrum test
[0063] The infrared spectrum test of sample 1-1# was carried out on Nicolet iS10 Fourier infrared spectrometer of Thermo Fisher Scientific Inc., USA. The results are as follows: Figure 4 The characteristic absorption peaks in the infrared spectrum confirm the accuracy of the crystal structure.
[0064] (5) Thermogravimetric test
[0065] The thermogravimetric test of sample 1-1# was conducted on a TGA / DSC1 / 1100SF thermogravimetric analyzer manufactured by Mettler-Toledo International Trading (Shanghai) Co., Ltd. The results are shown in the figure below. Figure 5 As shown, the thermal decomposition temperature of this compound is 178°C.
[0066] (6) Frequency doubling test experiment and results
[0067] The SHG test experiment for sample 1-1# was conducted as follows: a Q-switched Nd:YAG solid-state laser with a wavelength of 1064 nm was used as the fundamental frequency to illuminate the crystal powder under test. The generated 532 nm second harmonic was detected using a photomultiplier tube, and the harmonic intensity was displayed on an oscilloscope. The test crystal sample and a standard KDP crystal were ground separately and sieved using a standard sieve to produce crystals of varying particle sizes: less than 50-74 μm, 74-105 μm, 105-150 μm, 150-200 μm, and 200-280 μm, respectively. The SHG signal was observed as a function of particle size to determine whether phase matching was achieved. Under identical test conditions, the intensity of the second harmonic generated by the sample was compared with that generated by the reference KDP crystal to determine the relative magnitude of the SHG effect.
[0068] The test results show that the compound α-(C2H5N4)(NO3) crystal has a strong powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, its frequency-doubled intensity is 3.50 times that of KDP crystal ( Figure 6 ), and can achieve phase matching ( Figure 7 ).
[0069] (7) Birefringence experiment and results
[0070] The birefringence test experiment of sample 1-1# is as follows: the optical path difference and crystal thickness of a specific crystal plane of the crystal material are obtained under a 546nm light source using a ZEISS AxioScope 5 polarizing microscope equipped with a Berek compensator. eˉ N o |×T=Δn×T to determine birefringence, the optical path difference is R, the measured birefringence is Δn, and the crystal thickness is T.
[0071] The test results show that Figure 8 In a, α-(C2H5N4)(NO3) did not undergo extinction; Figure 8 In b, the crystal is completely extinct and the optical path difference is 2.30 μm. Figure 8 As shown in Figure c, the crystal thickness of α-(C2H5N4)(NO3) is 33.419 μm. According to the formula R=Δn×T, the birefringence of the crystal is calculated to be 0.069.
[0072] Example 2
[0073] (1) Preparation of samples 2-1# to 2-8#
[0074] Table 2. Relationship between sample synthesis conditions and sample numbers
[0075]
[0076] An organic source (3-amino-1,2,4-triazole), an inorganic source (nitric acid), and water were mixed in a specific ratio to form a raw material. The mixture was placed in an open evaporating dish. After the aqueous solution slowly evaporated at the crystallization temperature, the solution was filtered, washed, and dried to obtain a colorless, blocky β-(C2H5N4)(NO3) crystal sample. The relationship between the types and ratios of the raw materials in the initial mixture, the crystallization temperature, the crystallization time, and the sample number is shown in Table 2.
[0077] (2) Crystal structure analysis of samples
[0078] The structures of samples 2-1# to 2-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0079] The single crystal X-ray diffraction was performed on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The crystal size was 0.32 × 0.27 × 0.11 mm. 3 The data collection temperature was 293K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure was solved using the SHELXTL-97 program package; the positions of heavy atoms were determined by direct method, and the coordinates of the remaining atoms were obtained by difference Fourier synthesis method; the F-based 2 The coordinates of all atoms and anisotropic thermal parameters were refined using the full-matrix least-squares method.
[0080] Single crystal X-ray diffraction results show that samples 2-1# to 2-8# have the same chemical formula and crystal structure, the chemical formula is β-(C2H5N4)(NO3), the molecular weight is 147.11, belongs to the monoclinic system, the space group is P21, and the unit cell parameters are β=88.32~92.14°,Z=8,unit cell volume is
[0081] Take sample 2-1# as a typical example, its crystal structure data is β=90.381(3)°,Z=8,unit cell volume is Its crystal structure is Figure 9 shown.
[0082] Powder X-ray diffraction was performed on a Bruker D8 X-ray powder diffractometer from Bruker, Germany, using a fixed-target monochromatic light source of Cu-Kα and a wavelength of The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.
[0083] The powder X-ray diffraction results show that the diffraction peaks of samples 2-1# to 2-8# in the XRD spectra are at the same position as the diffraction peaks fitted by the single crystal data.
[0084] Take sample 2-1# as a typical example. Figure 10 The X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction and the X-ray diffraction pattern obtained by powdered sample 2-1# show consistent peak positions and intensities, indicating that the obtained sample is of high purity.
[0085] (3) UV-visible-near infrared spectroscopy test
[0086] The UV-visible transmission spectrum of sample 2-1# was tested on a Carry5000 UV-visible-near-infrared spectrophotometer from Agilent Technologies, USA. Figure 11 As shown, the ultraviolet absorption cutoff edge of the compound is 248 nm and the optical band gap is 5.00 eV.
[0087] (4) Infrared spectrum test
[0088] The infrared spectrum test of sample 2-1# was carried out on Nicolet iS10 Fourier infrared spectrometer of Thermo Fisher Scientific Inc., USA. The results are as follows: Figure 12 The characteristic absorption peaks in the infrared spectrum confirm the accuracy of the crystal structure.
[0089] (5) Thermogravimetric test
[0090] The thermogravimetric test of sample 2-1# was conducted on a TGA / DSC1 / 1100SF thermogravimetric analyzer manufactured by Mettler-Toledo International Trading (Shanghai) Co., Ltd. The results are shown in the figure below. Figure 13 As shown, the thermal decomposition temperature of this compound is 176°C.
[0091] (6) Frequency doubling test experiment and results
[0092] The SHG test experiment for sample 2-1# was conducted as follows: a Q-switched Nd:YAG solid-state laser with a wavelength of 1064 nm was used as the fundamental frequency to illuminate the crystal powder under test. A photomultiplier tube was used to detect the generated 532 nm second harmonic, and an oscilloscope was used to display the harmonic intensity. The test crystal sample and a standard KDP crystal were ground separately and sieved using a standard sieve to produce crystals of varying particle sizes: less than 50-74 μm, 74-105 μm, 105-150 μm, 150-200 μm, and 200-280 μm, respectively. The SHG signal was observed as a function of particle size to determine whether phase matching was achieved. Under identical test conditions, the intensity of the second harmonic generated by the sample was compared with that generated by the reference KDP crystal to determine the relative magnitude of the SHG effect.
[0093] The test results show that the compound β-(C2H5N4)(NO3) crystal has a strong powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, its frequency-doubled intensity is 1.00 times that of KDP crystal ( Figure 14 ), and can achieve phase matching ( Figure 15 ).
[0094] (7) Birefringence experiment and results
[0095] The birefringence test experiment of sample 2-1# is as follows:
[0096] The optical path difference and crystal thickness of a specific crystal plane of the crystal material were obtained using a ZEISS Axio Scope 5 polarizing microscope equipped with a Berek compensator under a 546 nm light source. eˉ N o |×T=Δn×T to determine birefringence, the optical path difference is R, the measured birefringence is Δn, and the crystal thickness is T.
[0097] The test results show that Figure 16 In a, β-(C2H5N4)(NO3) did not undergo extinction; Figure 16 In b, the crystal is completely extinct and the optical path difference is 1.88 μm. Figure 16 As shown in Figure c, the crystal thickness of β-(C2H5N4)(NO3) is 40.708 μm. According to the formula R=Δn×T, the birefringence of the crystal is calculated to be 0.046.
[0098] In the above embodiments, unless otherwise specified, materials or processing techniques are conventional commercial products or conventional techniques in the art.
[0099] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.
Claims
1. A polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate, characterized in that: The chemical formula of the crystalline material is (C2H5N4)(NO3), with a molecular weight of 147.11, and it includes two types: α-(C2H5N4)(NO3) and β-(C2H5N4)(NO3); The α-(C2H5N4)(NO3) crystallizes in the triclinic system with a space group of P1 and unit cell parameters of α=110.44~114.63°,β=93.04~97.71°,γ=93.49~97.64°,Z=2,unit cell volume is The β-(C2H5N4)(NO3) crystallizes in the monoclinic system with a space group of P21 and unit cell parameters of β=88.32~92.14°,Z=8,unit cell volume is 2. The method for preparing a polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate according to claim 1, characterized in that: When the crystal material is α-(C2H5N4)(NO3), the preparation method is specifically as follows: An organic source, an inorganic source and water are mixed in a certain stoichiometric ratio to form an initial mixed raw material, and the obtained solution is placed in an open evaporating dish for volatilization and crystallization to precipitate a colorless and transparent crystal form α, which is the α-(C2H5N4)(NO3) crystal material; The organic source is 3-amino-1,2,4-triazole; The inorganic source is nitric acid; The molar ratio of the organic source, the inorganic source and water in the initial mixed raw material is 10:(10-60):(500-1250); the volatilization temperature is 10-45 DEG C; and the volatilization time is not less than one week.
3. The method for preparing a polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate according to claim 1, characterized in that: When the crystalline material is β-(C2H5N4)(NO3), the preparation method is specifically as follows: An organic source, an inorganic source and water are mixed in a certain stoichiometric ratio to form an initial mixed raw material, and the obtained solution is placed in an open evaporating dish for volatilization and crystallization to precipitate a colorless and transparent crystalline form β, namely β-(C2H5N4)(NO3) crystalline material; The organic source is 3-amino-1,2,4-triazole; The inorganic source is nitric acid; The molar ratio of the organic source, the inorganic source and water in the initial mixed raw material is 10:(70-120):(500-1250); the volatilization temperature is 10-45 DEG C; and the volatilization time is not less than one week.
4. Use of the polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate as claimed in claim 1 in laser frequency converters, optical parametric amplifiers, optical parametric oscillators and photoelectric rectifiers.
5. Use of the polymorphic nonlinear optical crystal material of 3-amino-1,2,4-triazole nitrate according to claim 4, characterized in that: The crystal material can be used in a laser frequency converter to output 532nm laser under 1064nm laser irradiation.
Citation Information
Patent Citations
Mercury-based nitrate second-order nonlinear optical crystal material and preparation and application thereof
CN116949575A